NEUROTICISM DAN CORONAVIRUS ANXIETY PADA PENYINTAS COVID 19 - Muhammad Afif Alhad; Inayah Ulum Mufidah; Hajar Maqshuroh; Florenxe Naully Gloria Panjaitan (Universitas Sahid Surakarta, 2023)
The COVID-19 pandemic has been in its third year. The psychological impact remains undergone by many people especially those who had experienced positive testing of COVID 19, including anxiety. One of the causes of anxiety is because of the massive information exposure about Covid 19 or in current condition called coronavirus anxiety. One of the personality traits that is prone to anxiety is neuroticism. This research tried to find out whether Covid 19 survivors with the neuroticism personality trait had a tendency to experience anxiety due to the exposure to information about Covid 19. A total of 120 respondents obtained through purposive sampling participated in this study. Based on the results of the analysis using simple linear regression, it could be concluded that the neuroticism personality trait had a positive correlation with coronavirus anxiety, which indicated that Covid 19 survivors with high levels of neuroticism had a tendency to experience coronavirus anxiety. In addition, the results of the analysis also showed that the neuroticism personality trait explained 25.1% variance of coronavirus anxiety.